Bounty of greed [large type] : the Lincoln County War - Colt, Paul (Wheeler Publishing, a part of Gale, a Cengage Company, 2018)
"Powerful merchant and political strongman James Dolan owns Lincoln County, until brash young English businessman John Turnstall hits town to challenge his empire. War breaks out when Turnstall is murdered. William Bonney vows revenge, launching the legendary outlaw career of Billy the Kid. Gunmen calling themselves Regulators hunt down and kill those responsible for Turnstall's murder. Deputy U.S. Marshal Ty Ledger is caught between determined forces in a bloody confrontation that comes to a fiery climax when the army is called in."--Back cover.